The introduction of street art's etymology-related context and discipline against an artwork in the public space / Syafril Amir Muhammad and Nurul Huda Mohd Din - Muhammad, Syafril Amir; Mohd Din, Nurul Huda (Universiti Teknologi MARA, Perak, 2023)
This paper provides an introduction and overview of the term ‘street art’. Related artwork in outdoor public areas such as ‘graffiti’, ‘murals’, and ‘public art’ are also debated to gain an understanding of the terms. Since the late 1960s, graffiti has developed in the United States and had a huge impact on the atmosphere of Western art and the development of art knowledge. The distinctions between different terminologies reflect the understanding of artists, scholars, academics, researchers, and the public. This review will be investigated using a conceptual of etymological perspective. This discussion also considers the publication and influence of artists such as John Fekner, David Wojnarowicz, Richard Hembleton, and Keith Haring at the beginning of the existence of artistic genres. This is necessary because the term "street art" is frequently used interchangeably in a few publications and discussions. Based on this review, three additional recommendations are made for the following researcher to do a series of studies.